Identitas Gastronomi dan Perspektif Pariwisata yang Berkelanjutan - Putra, Mandradhitya Kusuma (Jurnal Ilmiah Pariwisata; Vol 26 No 1 (2021): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v26i1.1471, 2021)
Gastronomy is one of the main reason for people to visit certain places. Furthermore, it often reflects tourism destination cultural identity where most researcher found a strong relationship with the development of sustainable tourism. This research aimed to evaluate the identity of Cirebon as capital of gastronomy tourism in West Java and its role in creating sustainable tourism experience. It was qualitative approach research with triangulation data collection method and used an in-depth interview involving 15 respondents from tourists, private sector and government official representatives. SWOT analysis and flow model analysis were then conducted to obtain the findings. Researcher found that Cirebon’s gastronomy tourism identity is the result of melting pot of culture between Chinese, Arabs, India and Indonesia. It is then highly influenced with the availability of local commodities, native technic of producing food, prevailing norms, religion and believes, and socially controlled culture. Hence, the impact on sustainable tourism experience is profoundly high. This research is expected to give contribution in developing gastronomy tourism in Cirebon and as reference in more researches related with sustainable gastronomy tourism experience in general. Keywords : Gastronomi Tourism; Sustainable Tourism Development